Responses of vascular plant fine roots and associated microbial communities to whole-ecosystem warming and elevated CO2 in northern peatlands - Duchesneau, Katherine (The New phytologist, 2024)
© 2024 The Authors. New Phytologist © 2024 New Phytologist Foundation.